KEPEMIMPINAN KEPALA SEKOLAH BERDASARKAN KECERDASAN EMOSIONAL DI MTS DARUL AMAL MULYOJATI KECAMATAN METRO BARAT KOTA METRO - Nurhidyah, Betty; Hidayati Murtafiah, Nurul; Mujiyatun (UNISAN JURNAL, 2024)
Leadership The Foundation has an integrated relationship with Emotional Intelligence in Educational Institutions . Meanwhile , this study aims to find out and reveal the Leadership of the Chairperson of the Foundation Based on Emotional Intelligence ( Eq ) at the MTS Darul Amal Mulyojati Kecamatan Metro Barat Educational Institution Sukabumi District , Bandar Lampung , Academic year 2022 / 2023. This research is a descriptive qualitative research focused on field research while the object of this research is the Leadership of the Chairperson of the Foundation Based on Emotional Intelligence ( Eq ) in the MTS Darul Amal Mulyojati Kecamatan Metro Barat Educational Institution Academic Year 2022/2023. Data was collected through documentation, interviews, and observation. Furthermore, the data was analyzed using various stages of analysis such as data reduction, data presentation, drawing conclusions and data verification. The results of the study show that the Leadership of the Chair of the Foundation Based on Emotional Intelligence ( Eq ) in the MTS Darul Amal Mulyojati Kecamatan Metro Barat Educational Institution , Sukabumi District , Bandar Lampung is: 1.) Head of the Foundation MTS Darul Amal Mulyojati Kecamatan Metro Barat Educational Institution, has a high commitment to self-vision in the future. 2.) The head of the foundation takes an emotional approach to all residents within the educational institution. 3.) Anatomy-neurology of leadership Head of the foundation, When in a problem, it doesn’t drag on to the problem they are facing, they will view the problem from a positive side so they can make the best decision. own strengths and limitations, able to control emotions and demonstrate honesty and integrity, trustworthiness.